Students' Perceptions and Learning Experiences with Smartboard-Supported Islamic Religious Education: A Qualitative Study - Bayu Segara; Rini Rahman (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study investigates students' perceptions and learning experiences with Smartboard-supported Islamic Religious Education and explores the factors shaping these perceptions in a senior high school context. A descriptive qualitative design was employed at SMA Negeri 1 Pariaman, Indonesia, between May and June 2026. Participants were purposively selected and consisted of ten Grade XI F2 students, one Islamic Religious Education teacher, and one vice principal for curriculum affairs. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The trustworthiness of the findings was established through source and method triangulation and member checking. The findings reveal that students generally developed positive perceptions of Smartboard-supported learning through three interrelated stages: receiving, understanding, and evaluation. Smartboard enhanced students' affective, cognitive, and social learning experiences by increasing classroom engagement, conceptual understanding, collaborative participation, and access to diverse digital learning resources. Students' perceptions were shaped by the interaction of perceiver factors (learning preferences), target factors (interactive multimedia features and internet connectivity), and situational factors (teacher competence, school policy, and technological infrastructure). Unlike previous studies that primarily emphasized learning outcomes or technology acceptance in general education, this study qualitatively integrates Walgito's perception theory and Robbins and Judge's Perceiver–Target–Situation framework to explain students' learning experiences within Smartboard-supported Islamic Religious Education. The study enriches theoretical discussions on digital pedagogy in religious education and provides practical recommendations for integrating interactive technologies through pedagogically meaningful, student-centered learning environments.